1981
DOI: 10.1113/jphysiol.1981.sp013695
|View full text |Cite
|
Sign up to set email alerts
|

The direction of growth of differentiating neurones and myoblasts from frog embryos in an applied electric field.

Abstract: 4. Applied electric fields had no effect on the location of the origin of neurites on the cell body.5. Spherical myoblasts cultured in applied electric fields (36-170 mV/mm) elongated with a bipolar axis of growth which was perpendicular to the electric field. The response was graded and disappeared at field strengths below 36 mV/mm. 6. It is suggested that in vivo, the direction of neural outgrowth from the neural tube and the strict spatial organization of somites might be under the control, in part, of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
169
2
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(185 citation statements)
references
References 29 publications
(35 reference statements)
13
169
2
1
Order By: Relevance
“…As we stated in a preliminary report of this phenomenon (30), this is the first example of galvanotaxis in embryonic cells and only the second case of perpendicular orientation (the first being Xenopus muscle cell elongation [16]) . Recently, two other laboratories have independently found that amphibian neural crest cells exhibit the same three types of response to steady fields (40, 7), and we have also observed the orientation response in quail neural crest cells (12,30).…”
Section: New Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we stated in a preliminary report of this phenomenon (30), this is the first example of galvanotaxis in embryonic cells and only the second case of perpendicular orientation (the first being Xenopus muscle cell elongation [16]) . Recently, two other laboratories have independently found that amphibian neural crest cells exhibit the same three types of response to steady fields (40, 7), and we have also observed the orientation response in quail neural crest cells (12,30).…”
Section: New Findingsmentioning
confidence: 99%
“…Recently, a related phenomenon of embryonic cell galvanotropism has also been observed in developing neurons. This cell type grows toward the cathode in a DC electric field (19,16,13,33). It is important to note that the field strengths that elicit these galvanotropic and galvanotactic responses in vitro are quite small and may well be generated in vivo.…”
mentioning
confidence: 99%
“…However, after a lag period of 30 min following the exposure to voltage gradient, the neurites facing the anode start to regress as if being repelled by the anodal electrode. Further clarification on the response of applied Direct Current (DC) voltages on single nerve fibres was shown by Hinkle et al [40] and Patel & Poo [64]. They observed that the neurites that were parallel to the field grow towards the cathode, while the ones that were perpendicular to the electric field turned in order to grow towards the cathode.…”
Section: Applied Electrical Fields For Axonal Regenerationmentioning
confidence: 95%
“…Borgens et al [112][113][114][115] reported that the spinal cord responded to damage by generating large and persistent electrical signals, and in turn applied electric stimulation promoted spinal cord repair in human and other mammals. Hinkle et al [86,92,[124][125][126][127][128][129][130][131][132][133] reported that many vitro experiments showed that the electric fields were equivalent to those measured in vivo control important cell behaviors such as directional cell migration (galvanotaxis or electrotaxis), cell division orientation, and cell cycle control.…”
Section: Pathophysiological and Biological Significance Of Spontaneoumentioning
confidence: 99%